Hepatitis B virus X protein and TGF-β: partners in the carcinogenic journey of hepatocellular carcinoma - Yan, Wei; Rao, Dean; Fan, Feimu; Liang, Huifang; Zhang, Zunyi; Dong, Hanhua (Frontiers in Oncology, 2024)
Hepatitis B infection is substantially associated with the development of liver cancer globally, with the prevalence of hepatocellular carcinoma (HCC) cases exceeding 50%. Hepatitis B virus (HBV) encodes the Hepatitis B virus X (HBx) protein, a pleiotropic regulatory protein necessary for the transcription of the HBV covalently closed circular DNA (cccDNA) microchromosome. In previous studies, HBV-associated HCC was revealed to be affected by HBx in multiple signaling pathways, resulting in genetic mutations and epigenetic modifications in proto-oncogenes and tumor suppressor genes. In addition, transforming growth factor-β (TGF-β) has dichotomous potentials at various phases of malignancy as it is a crucial signaling pathway that regulates multiple cellular and physiological processes. In early HCC, TGF-β has a significant antitumor effect, whereas in advanced HCC, it promotes malignant progression. TGF-β interacts with the HBx protein in HCC, regulating the pathogenesis of HCC. This review summarizes the respective and dcombined functions of HBx and TGB-β in HCC occurrence and development.